Genetic algorithm approach to cell formation and machine selection problems in the scheduling of cellular manufacturing - Pang, Bin Teck (2008)
This project presents a different approach by using genetic algorithm conducted to compare the work by Beaulieu et al. (1997) in the scheduling of a cellular manufacturing system. Both approaches consider explicitly the main elements of manufacturing costs including fixed and variable costs in operations.